Carbon Materials in Perovskite Solar Cells: Prospects and Future Challenges. Issue 2 (22nd June 2019) - Ferguson, Victoria; Silva, S. Ravi P.; Zhang, Wei
Abstract : Metal halide perovskite solar cells are emerging candidates for next‐generation thin‐film photovoltaic devices with the potential for extremely low fabrication cost and high power conversion efficiency. Perovskite solar cells have demonstrated a rapid development in device performance over the last decade, from an initial 3.81% to a most recently certified 24.2%, though the challenges of long‐term stability and lead toxicity still remain. Carbon materials, ranging from zero‐dimensional carbon quantum dots to three‐dimensional carbon black materials, are promising candidates for the enhancement of both efficiency and stability of perovskite solar cells, offering unique advantages for incorporation into various device architectures. In this review article, we present a concise overview of important and exciting advancements of perovskite solar cells that incorporate different dimensions of carbon material in their device architectures in an effort to simultaneously improve device performance and long‐term stability. We also discuss the major advantages and potential challenges of each technique that has been developed in the most recent work. Finally, we outline the future opportunities toward more efficient and stable perovskite solar cells utilizing carbon materials. Abstract : Carbon materials are promising candidates for the enhancement of both efficiency and stability of perovskite solar cells. This review provides an overview of perovskite solar cells that incorporate different dimensions of carbon material in their device architecture. The potential benefits of each dimension of carbon are highlighted, and future methods of incorporation are suggested.